The effect of Chinese herbal medicine on male factor infertility: study protocol for a randomized controlled trial - Wen, Qidan; Xu, Huanying; Zou, Haoxi; Wang, Pei; Xing, Xiaoyan; Chen, Ying; Zhu, Qiaoling; Chen, Yu; Tan, Minhua; Zhang, Miaomiao; Pan, Ting; Chen, Yanfen; et al. (Frontiers in Endocrinology, 2024)
The global prevalence of infertility is 9%, with male factors potentially accounting for 40% to 60% of cases. Conventional treatments can be ineffective, invasive, costly, and linked to adverse effects and high risks. Previous studies have shown that, Chinese herbal medicine (CHM) can regulate the hypothalamus-pituitary-testis axis, improve sperm abnormalities and quality, mitigate oxidative stress, and decrease DNA fragmentation index (DFI). Yet, the evidence backing the use of Chinese herbal medicine (CHM) for treating male factor infertility lacks conviction due to study design limitations, and there remains a scarcity of studies on the live birth rate following CHM treatment for male factor infertility. Here, we describe the rationale and design of a randomized waitlist-controlled trial to evaluate the effect of CHM on the live birth rate among males with infertility.Methods: This study is a single-center, randomized, waitlist-controlled study. A total of 250 couples diagnosed with male factor infertility will be enrolled in this study and then randomly allocated into two groups in a 1:1 ratio. Male participants in CHM group (treatment group) will receive CHM once a day for 3 months. Male participants in the waitlist group (control group) will not receive any treatment for 3 months. After 3 months, participants in both groups need to be followed up for another 12 months. The primary outcome will be the live birth rate; secondary outcomes include semen quality parameters, DFI and pregnancy related outcomes. Safety will also be assessed.The purpose of this trial is to explore the effects and safety of CHM on the live birth rate among couples dealing with male factor infertility. The outcome of this trial may provide a viable treatment option for male factor infertility.